2021
DOI: 10.15294/edaj.v10i2.43092
|View full text |Cite
|
Sign up to set email alerts
|

Macroprudential Policy and Credit Risk in Dual Banking System

Abstract: Issues related to financial stability are a very complex problem, especially the global crisis impact in 2008. Based on these conditions, the Basel Committee on Banking Supervision introduced a macroprudential policy to mitigate financial system risk systemically. The study aims to analyze the impact of macroprudential policy on the banks’ risk exposure by adopting credit risk as a risk proxy. By adopting a panel dynamic approach, credit risk is used to be a dependent variable while independent variables con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, no attention has been given to capture the LR. C RR and LR remain unaccounted by Mustain and Fakhrunnas (2021).…”
Section: Macroprudential Policies and Bank Riskmentioning
confidence: 97%
See 3 more Smart Citations
“…However, no attention has been given to capture the LR. C RR and LR remain unaccounted by Mustain and Fakhrunnas (2021).…”
Section: Macroprudential Policies and Bank Riskmentioning
confidence: 97%
“…The MPP is important as just relying on the microprudential policies will cause the trickle-down effect in whole system, as it is evident from the latest incident of subprime crisis. Recentl y Mustain and Fakhrunnas (2021) found that MPPs are effective in mitigating the BR. However, the effect of these MPPs on BR varies as per bank balance sheet characteristics such as liquidity and CRR.…”
Section: Bank's Audited Accountsmentioning
confidence: 99%
See 2 more Smart Citations
“…These crises highlight the importance of explaining the relationship between economic conditions and the health of the banking system. Because during the crises, the level of claims increases sharply, a significant amount of banking resources is depleted [4]. Explaining the above relationship, which is more important during the financial crises, leads to identifying the strength of the banking system, especially from the point of view of default of payment facilities in times of banking crises.…”
Section: Introductionmentioning
confidence: 99%